THE CORRELATION BETWEEN PERSONAL HYGIENE OF ADOLESCENT GIRLS DURING MENSTRUATION TOWARD THE INCIDENCE OF PRURITUS VULVAE AT ONE OF THE HIGH SCHOOLS IN DOLOK SANGGUL - Nainggolan, Angeli Stephanie; Hasugian, Rosinta; Simamora, Yossy Sheren; Cathryne, Joice; Debby, Chryest (Universitas Pelita Harapan, 2024)
Pruritus vulvae is an itching sensation in the female genitalia area during menstruation. As many as 5.2 million Indonesian adolescent girls often complain of pruritus vulvae after menstruation due to poor personal hygiene behavior. According to the results of an initial survey of 25 students at one of the high schools in Dolok Sanggul, all students experienced itching in the female genital area during menstruation. The purpose of this study is to investigate whether menstrual hygiene practices and the incidence of pruritus vulvae are related in adolescent girls at one of the high schools in Dolok Sanggul. This study used an analytic quantitative method with a cross-sectional design. The sample for this study was 41 female students using the accidental sampling technique. The research instrument used a questionnaire on the relationship between personal hygiene behavior and the incidence of pruritus vulvae. This research was conducted in February-April 2023. The results of this study showed that 63.4% of class XII students had sufficient personal hygiene behavior during menstruation, and 82.9% of respondents did not experience pruritus vulvae. In this study, personal hygiene behavior towards pruritus vulvae had no relationship, as evidenced by the results of the Chi-square test, p-value = 0.629 (p< 0.05). It is hoped that further research can be conducted by adding research variables and the number of respondents.